Research on the effectiveness of TPACK training module for University Teachers in Qingdao - He Sun; Nur Suhaidah Sukor; Noraini Said; Xianjun Dai (Human Resource Management Academic Research Society, 2025)
This study investigates the effectiveness of a specially designed TPACK training module tailored for university teachers at Qingdao University. The TPACK module was developed based on the needs of university educators and validated by experts. To implement and evaluate the impact of the training, 37 university teachers voluntarily participated in a threemonth blended training program. Data collection employed a pre-test and post-test design to assess the effectiveness of the TPACK module. The study contributes to educational management by emphasizing the critical role of targeted, integrated, and practical training modules. The training also enhanced university teachers' self-efficacy, confidence, and commitment to effectively integrating information technology into classroom teaching and management. This research deepens our understanding of teacher development and provides broader implications for educational management development, offering valuable insights for educational administrators and trainers aiming at foster innovation and technology proficiency among university educators.